Using basic MANET routing algorithms for data dissemination in vehicular Ad Hoc Networks (VANETs) - Samaras, Nicholas S. (2016 24th Telecommunications Forum (TELFOR), 2016)
Intelligent Transportation Systems (ITS) constitute a stimulating research subject for the global research community, as it is arguably considered to play a dominant role in the development of efficient, secure and safe transportation systems. ITS enable rapidly emerging information technologies and novel mobile applications and services in vehicles and transportation infrastructures. The development of inter/intra-vehicle and infrastructure-to-vehicle communication is one of the most challenging and critical issues for the ITS industry and data dissemination is crucial to the successful development of such systems. In this paper, we attempt to establish a basic framework on how pertinent is the use of some well-known Mobile Ad Hoc Networks (MANETs) routing algorithms in the analysis of data dissemination in VANETs. The interesting results are confirmed via simulation experiments.